Publicaciones periódicas y seriadas socialistas, 1899-1951 ([Centro de Documentación e Investigación de la Cultura de Izquierdas en la Argentina], 2006)
Collection of socialist oriented publications published in Argentina, 1899-1951, with some material covering up to 1990.